The formulation of inferential questions improves the understanding of continued texts - Salazar-Pisfil, Diego E. (2021)
The following research was developed aiming at knowing if the formulation of inferential questions improves the understanding  of continued texts at a private institute in Lima. This is an quantitative approach inquiry, with quasi-experimental design, (people in the control and experimental group were not assigned randomly and were not paired due to the fact that the groups were already formed. They existed before the experiment). The technique used was the survey and the instrument: the questionnaire with pretest and posttest, whose reliability coefficient was 0.093085389 (excellent). Results were analyzed and detailed accordingly. They were based on statistical average, standard deviation and the variance. Moreover, parametric statistics was applied at the level of <0,05. Statistics results were 0,00000000000003. It was demonstrated that the inferential questions formulation improves the understanding of continued texts in students at a private institute in Lima.